Entrepreneurship Competencies in Head of School Implementation of Integrated Quality Management SMP Negeri 7 Salatiga - Yuni Budyastuti; Bambang Sumadjoko; Patience Narimo (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe the competence of principals in implementing total quality management at SMP Negeri 7 Salatiga through entrepreneurial competence with three detailed tasks according to Permendikbud Number 15th 2018 namely: (1) planning an entrepreneurship development program, (2) implementing an entrepreneurship development program, (3) carry out an evaluation of the entrepreneurship program. This research is a qualitative with a phenomenological design. The data sources of this research are principals, teachers, administrative employees. The data obtained were analyzed through the stages of data collection, data reduction, data presentation and drawing conclusions. Data triangulation is used to check the validity of the data. The results showed that the entrepreneurial competence of the head of SMP Negeri 7 in implementing total quality management was realized by the success of the principal in planning an entrepreneurship development program by forming a team, delegating tasks, coordinating and socializing. In the implementation of the program the school principal succeeded by instilling innovative values, hard work, never giving up, strong motivation bringing the impact of quality improvement. While in the implementation of the evaluation of the entrepreneurship program with supervision, overcoming obstacles, and reporting on the implementation of each program as a reference for the next program.